2018
DOI: 10.1007/s10029-018-1854-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of postoperative complications after emergency repair of incarcerated groin hernia for adult patients: a retrospective cohort study

Abstract: Purpose This study aimed to explore risk factors of postoperative complications for adult patients with incarcerated groin hernia (IGH). Methods From January 2010 to December 2017, consecutive patients undergoing emergency hernia repair for IGH in our center were retrospectively reviewed. Postoperative complications, such as surgical site infection, seroma, hernia recurrence and mortality, were investigated, with risk factors for such complications analyzed using univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 32 publications
0
34
3
Order By: Relevance
“…However, if the contents are gangrenous, an urgent exploratory laparotomy with resection of gangrenous segment and anastomosis or ileostomy, depending on patients’ general condition, is the treatment of choice. Strangulated hernia increases the risks in emergency hernia repair, leading to an increased incidence of surgical site contamination and recurrence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, if the contents are gangrenous, an urgent exploratory laparotomy with resection of gangrenous segment and anastomosis or ileostomy, depending on patients’ general condition, is the treatment of choice. Strangulated hernia increases the risks in emergency hernia repair, leading to an increased incidence of surgical site contamination and recurrence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alvarez et al [2] observed that 13% of incarcerated groin hernia patients had undergone bowel resection surgery. Kurt et al [5] reported that bowel resection was required in approximately 15% of patents with an incarcerated groin hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Groin hernia, which is a combination of inguinal and femoral hernia, occurs in 27% of men and 3% of women [1] and is commonly encountered on a daily basis. Around 5%-15% of hernia patients have incarceration, and approximately 15% of cases may develop bowel necrosis requiring bowel resection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis showed that the first 3 years after laparotomy are the high-risk period for hernia development (92–97% incidence) [ 3 ]. The frequency of recurrent hernias after anterior abdominal wall surgery can reach 50% [ 4 5 6 ].…”
Section: Introductionmentioning
confidence: 99%